Evaporation of Water in the Process of Movement of its Large Masses Through a High-Temperature Gas Medium; Journal of Engineering Physics and Thermophysics; Vol. 88, iss. 5 - Zhdanova A. O. Alena Olegovna (2015, 2015)
Title screen